Identification of Rho-associated protein kinase-alpha as an insulin receptor substrate-1 binding protein. - Farah, Sahar. (University of Ottawa (Canada), 1998)
Insulin receptor substrate-1 (IRS-1) is phosphorylated on multiple tyrosine residues by ligand-activated insulin receptor. These tyrosine phosphorylation sites serve to dock several SH2-containing signaling proteins. In addition, IRS-1 also contains several protein modules that have been implicated in protein-protein or protein-lipid interactions. In an attempt to identify novel proteins that may interact with these IRS-1 protein modules, yeast two-hybrid screening was employed. The bait, corresponding to the N-terminal 500 amino acids of the Xenopus IRS-1 (XIRS-1), was comprised of a pleckstrin homology (PH) domain, a phosphotyrosine binding (PTB) domain and a SAIN (Shc and IRS-1 NPXY binding) domain. Screening of a Xenopus oocyte cDNA library with the bait resulted in the isolation of a partial Xenopus cDNA, XROK$\alpha$. The cloned cDNA contains an open reading frame of about 500 amino acids (in frame with the N-terminal GAL4 activating domain) which are 90% identical to the C-terminus of the recently identified RhoA-associated protein kinase $\alpha$ (ROK$\alpha$). The partial XROK$\alpha$ cDNA contains the putative Rho binding domain as well as the C-terminal pleckstrin homology/cysteine rich domain (PH/CRD) but lacks the N-terminal serine/threonine kinase domain. Using the yeast two-hybrid system, we showed that XROK$\alpha$ interacts strongly with a constitutively active form of RhoA (V14-RhoA). Further analysis indicated that the XIRS-1 PTB domain is specifically involved in binding to XROK$\alpha$. To further characterize the potential role of XROK$\alpha$ in insulin signalling, I have cloned the entire coding sequence of XROK$\alpha$ by a combination of hybridyzation screening and PCR amplification. I have also generated XROK$\alpha$ specific polyclonal antibodies. Using these antibodies I have detected endogenous XROK $\alpha$ protein by both Western-blotting and by immune kinase assay in vitro. Taken together, these studies have identified an IRS-1 binding serine/threonine kinase which may play an important role in modulating insulin signalling.
Keywords: Biology, Molecular.